(untitled) (Eurasian Journal of Philology Science and Education, 2025)
In the age of technological development, the accurate translation of technical texts is crucial for international cooperation. This article is devoted to the challenges and strategies of technical translations between the English, Russian and Kazakh languages. The aim of the study is to identify how scientific meaning is preserved, adapted or slightly modified across languages. Qualitative, descriptive and comparative methods of research were used to analyze the examples taken from the book “Practical Electronics for Inventors” and their Russian and Kazakh translations. The analysis mainly focused on technical terms, complex noun phrases, symbols of technical discourse. According to the results of the research, literal translation dominates in the translation of technical terms. Literal translation ensures accuracy and consistency. Modulation and transposition are used to achieve grammatical coherence in the target language. In Kazakh translations the meaning is often adapted to fit the natural flow of the language. In Russian translations small clarifications are added to meet academic style requirements. Theoretically, this article contributes to translation studies by discussing the methods used by translators in multilingual technical context. Practically, it offers guidance for translators training. The insights can assist in improving the quality of technical translations in both professional and educational context. Keywords: technical translation, translation strategies, literal translation, multilingual translation, terminology management.